Selected B- Vitamins and Homocysteine Levels, and Methylenetetrahydrofolate Reductase 677C>T Polymorphism in Universiti Putra Malaysia - Chew, Siew Choo (2011)
Information on the MTHFR 677 C>T polymorphism and nutritional research involving B vitamins and homocysteine is limited, especially in developing countries such as Malaysia. As a result, this causes paucity in providing an overall picture of folate and homocysteine status by taking into account the genotyping aspect. Thus, this study investigated the nutritional folate intake and its blood status, focusing on the relationship of B-group vitamins (vitamin B6 and B12), serum homocysteine and the MTHFR 677 C>T polymorphism. The study subjects were identified by simple random sampling consisting of 54 Chinese and 46 Malays at Universiti Putra Malaysia, Serdang. Dietary folate intake was assessed with 24-hour dietary recall and a food -frequency questionnaire (FFQ). Biochemical assessment for serum and red blood cell (RBC) folate was carried out using microbiological assay, serum vitamin B12 with electrochemiluminescence immunoassay,and high-performance liquid chromatography for serum vitamin B6 and homocysteine. Polymerase chain reaction coupled with HinfI digestion was used for detection of MTHFR 677 C>T polymorphism. Based on 24-hour dietary recall, the mean dietary folate intake for men and women were 260.28 and 321.93 μg/day, respectively, which equal to 65% and 81% of Malaysian Recommended Nutrient Intake (RNI). The Chinese subjects had significantly higher folate intake compared to Malay subjects with 325.45 and 261.51 g/day, respectively, which is equal to 81% and 65% of RNI. Based on FFQ, the main dietary sources of folate were cereals, eggs and dairy products. Overall, the mean serum folate was 9.42 nmol/L, RBC folate was 209.72 nmol/L, serum vitamin B12 was 460.37 pmol/L, serum vitamin B6 was 22.14 nmol/L, and serum homocysteine was 14.54 mol/L. The folate deficiency reported to be 27% for serum and 78% for RBC, while for B6 and B12, both were 37% and 5%, respectively. As for homocysteine, the percentage elevation was almost half with 54%. Men had significantly lower folate levels than women. Comparing with ethnicity, Chinese showed significantly higher folate and vitamin B12 levels but lower homocysteine and vitamin B6 levels than the Malay subjects. Serum and RBC folate, serum vitamin B6, and B12 were significantly inversely related to serum homocysteine for all sexes and ethnicities. A higher prevalence of homozygous genotype was found among the Chinese subjects. Overall, the distribution of normal, heterozygous and homozygous genotypes was 57, 30, and 13%, respectively. The folate levels differed significantly for heterozygous and homozygous genotypes under different folate intake. Similarly, the effect of homozygous genotype on homocysteine levels was more prominent under low folate intake. Blood folate, vitamin B6 and B12 were higher in normal genotype for both ethnicities whereas subjects with heterozygous and homozygous genotype showed the highest homocysteine levels. In conclusion, high dietary folate intake helps to increase serum folate and lower the serum homocysteine levels. Individuals with the homozygous genotype were particularly sensitive to the status of several B vitamins (folate, vitamin B6, and B12). These results demonstrate an interaction between serum folate and MTHFR genotype in predicting homocysteine levels. This indicates that subjects with homozygous genotype have a higher folate requirement.